Effect of preoperative chemoradiotherapy on the immunological status of rectal cancer patients. (16th July 2020) - Yasui, Kazuaki; Kondou, Ryota; Iizuka, Akira; Miyata, Haruo; Tanaka, Emiko; Ashizawa, Tadashi; Nagashima, Takeshi; Ohshima, Keiichi; Urakami, Kenichi; Kusuhara, Masatoshi; Muramatsu, Koji; Sugino, Takashi; et al.
Abstract: The aim of the study was to investigate the effect of chemo-radiation on the genetic and immunological status of rectal cancer patients who were treated with preoperative chemoradiotherapy (CRT). The expression of immune response-associated genes was compared between rectal cancer patients treated ( n = 9) and not-treated ( n = 10) with preoperative CRT using volcano plot analysis. Apoptosis and epithelial-to-mesenchymal transition (EMT) marker genes were analysed by quantitative PCR (qPCR). Other markers associated with the tumor microenvironment (TME), such as tumor-infiltrating lymphocytes (TIL) and immune checkpoint molecules, were investigated using immunohistochemistry (IHC). The clinical responses of preoperative CRT for 9 rectal cancer patients were all rated as stable disease, while the pathological tumor regression score (TRG) revealed 6 cases of grade2 and 3 cases of grade1. According to the genetic signature of colon cancers, treated tumors belonged to consensus molecular subtype ( CMS)4, while not-treated tumors had signatures of CMS2 or 3. CRT-treated tumors showed significant upregulation of EMT-associated genes, such as CDH2, TGF-beta and FGF, and cancer stem cell-associated genes. Additionally, qPCR and IHC demonstrated a suppressive immunological status derived from the upregulation of inflammatory cytokines (IL-6, IL-10 and TGF-beta) and immune checkpoint genes (B7-H3 and B7-H5) and from M2-type macrophage accumulation in the tumor. The induction of EMT and immune-suppressive status in the tumor after strong CRT treatment urges the development of a novel combined therapy that restores immune-suppression and inhibits EMT, ultimately leading to distant metastasis control.